A Ni-catalyzed asymmetric C(sp)–P cross-coupling reaction for the synthesis of P-stereogenic alkynylphosphines. Issue 5 (16th January 2023) - Zhang, Bin; Zhou, Wen-Qing; Liu, Xu-Teng; Sun, Yingying; Zhang, Qing-Wei
Abstract : A catalytic asymmetric C(sp)–P cross coupling reaction for the synthesis of P-stereogenic alkynylphosphines was realized. A series of alkynylphosphines which could be derivatized to useful phosphine compounds was synthesized with excellent enantioselectivities. Abstract : Due to the high reactivity of the triple bond, P-stereogenic alkynylphosphines could be easily derivatized, serving as universal building blocks for structurally diverse phosphine compounds. However, the synthesis of alkynylphosphines via direct P–C bond formation was unprecedented. Here, we report an efficient method for the synthesis of P-stereogenic alkynylphosphines with high enantioselectivity via a Ni-catalyzed asymmetric cross-coupling reaction. The reaction could tolerate a variety of functional groups, affording products that can be converted into useful phosphine derivatives.